2023
DOI: 10.1101/2023.03.15.23287332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADCC-activating antibodies correlate with protection against congenital human cytomegalovirus infection

Abstract: Human cytomegalovirus (HCMV) is the most common vertically transmitted infection worldwide, yet there are no licensed vaccines or therapeutics to prevent congenital HCMV (cCMV) infection. Emerging evidence from studies of natural infection and HCMV vaccine trials indicates that antibody Fc effector functions may defend against HCMV infection. We previously reported that antibody-dependent cellular phagocytosis (ADCP) and IgG activation of FcγRI/FcγRII were associated with reduced risk of cCMV transmission, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Although no consistent benefit of post-exposure HIG therapy has been demonstrated for cCMV infections across various human clinical trials, it appears that treatment dosage and pharmacokinetics are important parameters of efficacy and protection ( 1418 ). In line with these observations, we recently demonstrated that not neutralization, but IgG-Fc-gamma (Fcγ)-mediated anti-viral mechanisms by non-neutralizing IgG, specifically maternal plasma levels of antibody-dependent cellular phagocytosis (ADCP) and antibody-dependent cellular cytotoxicity (ADCC), correlate with a reduced risk of congenital infection ( 19, 20 ). Intriguingly, both ADCP and ADCC are mediated by Fcγ receptors (FcγRs) expressed by nearly all immune cells including neutrophils, macrophages and NK cells.…”
Section: Introductionmentioning
confidence: 72%
“…Although no consistent benefit of post-exposure HIG therapy has been demonstrated for cCMV infections across various human clinical trials, it appears that treatment dosage and pharmacokinetics are important parameters of efficacy and protection ( 1418 ). In line with these observations, we recently demonstrated that not neutralization, but IgG-Fc-gamma (Fcγ)-mediated anti-viral mechanisms by non-neutralizing IgG, specifically maternal plasma levels of antibody-dependent cellular phagocytosis (ADCP) and antibody-dependent cellular cytotoxicity (ADCC), correlate with a reduced risk of congenital infection ( 19, 20 ). Intriguingly, both ADCP and ADCC are mediated by Fcγ receptors (FcγRs) expressed by nearly all immune cells including neutrophils, macrophages and NK cells.…”
Section: Introductionmentioning
confidence: 72%
“…Fc-mediated effector responses, and ADCC in particular, have been thought to play a major role in control of infections that utilize cell-to-cell spread as a primary mode of dissemination, such as herpes simplex virus (HSV) and cytomegalovirus (CMV). Both of these viruses can cause severe disease in infected neonates, but maternal antiviral ADCC-mediating antibodies have been associated with protection from disseminated HSV infection and from vertical CMV transmission in clinical observational studies [ 6 , 31 ].…”
Section: Mechanisms Of Nnab-mediated Protectionmentioning
confidence: 99%
“…Clinical trials for vaccines targeting influenza virus [ 2 ] and HIV [ 3 ] found that protection was associated with nNAbs. Similarly, partial vaccine-mediated protection against human cytomegalovirus (HCMV) [ 4 ] and reduced risk of in utero HCMV transmission [ 5 , 6 ] has been associated with nNAbs.…”
Section: Introductionmentioning
confidence: 99%